2006
DOI: 10.1007/s11269-006-0079-z
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation, Productivity and Poverty Linkages in Irrigation Systems in Java, Indonesia

Abstract: This paper analyzes irrigation-poverty linkages, and determines how and to what extent irrigation contributes to poverty alleviation, and whether there are any spatial patterns in poverty in irrigation systems. It also identifies conditions under which irrigation has greater anti-poverty impacts. The analysis is based on primary data collected during the 2000-2001 agricultural year, from four selected irrigation systems and rainfed areas in Java. The results indicate that irrigation has significant poverty red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Agricultural productivity levels are low in Pakistan due to water scarcity and degraded land and water resources (Hussain et al, ; Hussain and Hanjra, ; Hussain et al, ). Wheat, which is the major staple food crop in Pakistan, is no exception as far as low productivity is concerned.…”
Section: Farm Household Characteristicsmentioning
confidence: 99%
“…Agricultural productivity levels are low in Pakistan due to water scarcity and degraded land and water resources (Hussain et al, ; Hussain and Hanjra, ; Hussain et al, ). Wheat, which is the major staple food crop in Pakistan, is no exception as far as low productivity is concerned.…”
Section: Farm Household Characteristicsmentioning
confidence: 99%
“…The smaller the irrigation systems with well-managed infrastructure, relatively equitable water distribution and diversified cropping patterns, the greater the impacts of irrigation. Improving the performance of irrigation systems by improving water distribution across locations and enhancing land and water productivity through diversifying cropping patterns would help improve agricultural performance in the presently low-productivity parts of the system (Hussain et al, 2006).…”
Section: Agricultural Developmentmentioning
confidence: 99%
“…In a mega study to explore the links between irrigation and poverty alleviation in six Asian countries (India, Pakistan, Bangladesh, China, Vietnam and Indonesia) covering 26 irrigation systems, it was revealed that irrigation did significantly reduce poverty as measured by household income; however, poverty was still high in irrigation systems, averaging 34% (it varied from 6 to 65%) with significant inter-and intra-country differences in poverty incidence in irrigation systems (Hussain, 2007a). The locational differences (upstream-downstream poverty differences in India of about 11%) in poverty were more pronounced in larger irrigation systems (surface irrigation), where locational inequities in water distribution and agricultural productivity differences were also high (Hussain et al, 2006;Hussain, 2007b). The impact of groundwater irrigation on agriculture and poverty reduction is greater (Bhattarai and Narayanamoorthy, 2003;Shah, 2004;Narayanamoorthy, 2007), which also holds true in the context of the findings of present study.…”
Section: Extent Of Povertymentioning
confidence: 99%
“…Giordano (2007) believes that the increasing pressure on agricultural water use comes at a time when rural poverty reduction and national food security are major national goals. Hussain et al (2006) showed that negative social and environmental consequences often hurt the poor more than the non poor because the poor lack political power and the financial resources to avoid the potentially adverse impacts of irrigation, from physical displacements to health risks and land degradation. Akpabio et al (2007) reported that irrigation can increase the yields of most crops.…”
Section: Introductionmentioning
confidence: 99%